1980
DOI: 10.1083/jcb.87.3.746
|View full text |Cite
|
Sign up to set email alerts
|

Occluding junctions and cytoskeletal components in a cultured transporting epithelium

Abstract: MDCK cells form uninterrupted monolayers and make occluding junctions similar to those of natural epithelia. This article explores the relationship between these junctions and the cytoskeleton by combining studies on the distribution of microfilaments and microtubules with the effect of drugs, such as colchicine and cytochalasin B, on the degree of tightness of the occluding junctions . To study the degree of tightness, monolayers were prepared by plating MDCK cells on nylon disks coated with collagen . Disks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(122 citation statements)
references
References 33 publications
11
110
1
Order By: Relevance
“…kept to a large extent the nonextracted cell shape at the phase contrast and EM levels. In agreement with previous observations (18,44), an actin-rich submembrane cytoskeleton was observed associated with both apical and basolateral surfaces of MDCK cells by rhodamine phalloidin fluorescence on semi-thin frozen sections; larger amounts of actin were detected on the apical surface due to the presence of microvilli ( Fig. 1 A).…”
Section: Plasma Membrane Proteins Of Mdck Cells Show Differential Extsupporting
confidence: 80%
“…kept to a large extent the nonextracted cell shape at the phase contrast and EM levels. In agreement with previous observations (18,44), an actin-rich submembrane cytoskeleton was observed associated with both apical and basolateral surfaces of MDCK cells by rhodamine phalloidin fluorescence on semi-thin frozen sections; larger amounts of actin were detected on the apical surface due to the presence of microvilli ( Fig. 1 A).…”
Section: Plasma Membrane Proteins Of Mdck Cells Show Differential Extsupporting
confidence: 80%
“…An important modulator of endothelial and epithelial permeability is the actin cytoskeleton through its interaction with TJ complex components (Meza et al, 1980;Madara, 1991;Lum & Malik, 1996;Blum et al, 1997). In dengue virus-infected HMEC-1, actin fibres forming the peripheral ring at the apical side were rapidly disorganized and possibly fragmented as actin aggregates were observed in the cytoplasm of infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that disarray of the actin ring tethered to the plasma membrane in the apical side of epithelial and endothelial cells disrupts the organization of the TJ complex and the permeability of confluent monolayers (Meza et al, 1980;Lum & Malik, 1996). Infected HMEC-1 showed disorganization of actin structures and the actin ring.…”
Section: Actin Cytoskeleton Rearrangements and Occludin Redistributiomentioning
confidence: 99%
See 1 more Smart Citation
“…To disrupt the cell-cell contact, we exploited the Ca 2þ dependence of cadherin binding (23). We first determined the cell morphology, traction force, and cell-cell force for cell pairs with mature cell contacts in calcium-containing media.…”
Section: (Si Text)mentioning
confidence: 99%